Mechanical and microseismic characteristics of sandstones subject to moderate low-frequency differential cyclic loading (DCL) followed by monotonic loading up to failure - Song, Zhengyang; Konietzky, Heinz; Wu, Yunfeng; Cai, Xin (Acta geotechnica, 2023)
This work aims to experimentally investigate the behaviour of sandstone drilled from an underground coal mine exposed to low-frequency cyclic loading with distinct loading/unloading rates, namely differential cyclic loading (DCL). Three loading modes with different loading/unloading rates were applied. The test results are presented and analysed in terms of dissipated energy ratio (DER), evolution of secant elastic moduli, stress–strain hysteresis and acoustic emission (AE) behaviours. The correlation between DER and maximum cyclic load level is revealed, and a novel method to predict the strength of the rock sample is proposed based on statistics of DER at failure. The hardening behaviour is observed during cyclic loading, which is characterized by gradual enhancement of the secant elastic moduli. The stress–strain hysteresis is determined, which shows that phase shift between stress–strain is loading/unloading rate-dependent. The evolution of AE counts and energy is documented and discussed with respect to the dissipated energy. The results indicate that patterns of AE evolution and Kaiser effect are both influenced by cyclic loading paths.